Justice Robert H. Jackson's unpublished opinion in Brown v. Board - O'Brien, David M. (University Press of Kansas, 2017)
"Brown v. Board of Education is widely recognized as one of the US Supreme Court's most important decisions in the twentieth century. Robert H. Jackson, an associate justice on the case, is generally considered one of the Court's most gifted writers. Though much has been written about Brown, citing the writing and remarks of the justices who participated in the 1954 decision, comparatively little has been said about Jackson or his unpublished opinion, which is sometimes even mistakenly taken as a dissenting opinion. This book visits Brown v. Board of Education from Jackson's perspective and, in doing so, offers a reinterpretation of the justice's thinking, and of the Supreme Court's decision making, in a ruling that continues to reverberate through the nation's politics and public life. Weaving together judicial biography, legal history, and judicial politics, [this book] provides a nuanced look at constitutional interpretation, and the intersection of law and politics, from inside the mind of a justice, within the context of a Court deciding a seminal case. Through an analysis of six drafts of Jackson's unpublished concurring opinion, David M. O'Brien explores the justice's evolving thoughts on relevant issues at critical moments in the case. His retelling of Brown presents a new view of longstanding arguments confronted by Jackson and the other justices over "original intent" versus a "living Constitution," the role of the Court, and social change and justice in American political life. The book includes the final draft of Jackson's unpublished opinion, as well as the Warren Court's opinions in Brown and in Bolling v. Sharpe, for comparison, along with a timeline of developments and decision making leading to the Court's landmark ruling."--Publisher's website